Si Embul: Assesment In Baby And Children To Increasing Haemoglobin Level In 6-24 Months Children - Yuliasti Eka Purnamaningrum; Abdul Latief; Setyo Rini Wijayanti; Dea Surya Lakshita (Poltekkes Kemenkes Surakarta, 2022)
Background: Iron deficiency anemia is one of the health problems in Indonesian children that need special attention because it has an impact not only for now but also on the upcoming time. The si Embul innovation program is a comprehensive activity that includes growth and development checks, evaluation of exclusive breastfeeding, identification of anemia by checking the baby’s hemoglobin, and consultations with nutritionists and doctors. Methods: This research used descriptive correlational with a cross-sectional research design. The sample was all children aged 6-24 months who are included in the Si Embul Program at the Tegalrejo Health Center in 2017-2019 as much as 149 children. The univariate analysis describes the characteristics of the research subjects. Relationship between the Si Embul Program and anemia status analyze using bivariate analysis, carried out with chi-square at a significant level of 5%. The research was carried out using secondary data in patient medical record and register books and taken from both books. Results: The incidence of anemia was more common in female respondents as many as 31 people (20.81%). Based on the baby's birth weight, the incidence of anemia was more common in BBLN (normal birth weight) as many as 50 people (33.55%). The Si Embul program was associated with anemia status in children aged 6-24 months with a p-value of 0.004 (p<0.05). Conclusion: The si Embul program was associated with anemia status in children aged 6-24 months with a p-value of 0.004. This shows that the excistence of Si embul program can reduce the incidence of anemia in children aged 6-24 months.